GERM-10. EARLY DETECTION OF CNS GERMINOMA IN PITUITARY STALK THICKENING USING NON-INVASIVE microRNA TESTING. Issue 2 (22nd June 2018) - Murray, Matthew; Verduci, Lorena; Kyle, Victoria; Ward, Dawn; Nicholson, James; Scarpini, Cinzia; Coleman, Nicholas
Abstract: INTRODUCTION: Patients presenting with diabetes insipidus (DI) and subtle pituitary-stalk thickening on MRI represent a management challenge. LCH and germinoma work-up (including serum/CSF AFP/HCG) is usually negative, given the poor sensitivity of these tests. Risks of neurosurgical biopsy in such cases often outweigh perceived benefits. Consequently, biopsy is often only performed for radiological progression. This suboptimal approach may cause diagnostic delay and inferior outcomes. Non-invasive diagnostic microRNA testing for malignant germ cell tumours (MGCTs) has shown substantial promise. Here, we highlight the potential for microRNAs to facilitate earlier diagnosis of CNS germinoma. METHODS: Using qRT-PCR, we quantified CSF miR-371a-3p levels at presentation in two patients (one 15yo male, PIT#1; one 12yo female, PIT#2), both with DI and 5mm pituitary-stalk thickening, and compared levels with those at diagnosis from six CNS-MGCT patients and two controls (one CNS neuroblastoma, one low-grade-glioma). RESULTS: One patient (PIT#1) had elevated CSF miR-371a-3p levels consistent with those seen in CNS-MGCT patients; the other (PIT#2) had levels similar to those seen in controls. Over a two year period of surveillance (2015-2017), and consistent with the abnormally elevated CSF-miR-371a-3p level, the PIT#1 case showed clear radiological progression and after further negative serum/CSF AFP/HCG work-up, biopsy confirmed germinoma. Conversely, the PIT#2 patient showed no change in pituitary-stalk thickening, but other radiological changes suggestive of neurodegenerative LCH. CONCLUSIONS: CSF microRNAs show potential for screening individuals presenting with DI and pituitary-stalk thickening to identify those who might benefit from early biopsy. Ultimately, completely non-invasive CNS-MGCT diagnosis may be feasible.